Systemic low-grade inflammation in post-traumatic stress disorder: a systematic review - Speer K; Upton D; Semple S; McKune A (Dove Medical Press, 2018)
Kathryn Speer,1 Dominic Upton,2 Stuart Semple,1,3 Andrew McKune1–4 1Discipline of Sport and Exercise Science, Faculty of Health, University of Canberra, Canberra, ACT, Australia; 2Faculty of Health, University of Canberra, Canberra, ACT, Australia; 3Research Institute for Sport and Exercise, University of Canberra, Canberra, ACT, Australia; 4Discipline of Biokinetics, Exercise and Leisure Sciences, School of Health Sciences, University of KwaZulu Natal, Durban, South Africa Abstract: Studies examining post-traumatic stress disorder (PTSD) have either emphasized a relationship between PTSD and a systemically pro-inflammatory state or identified a link between PTSD and chronic disease. The aim of this study was to evaluate the evidence for a relationship between individuals with PTSD and systemic low-grade inflammation that has been proposed to underlie chronic disease development in this population. The authors conducted a systematic review of the literature (January 2006 to April 2017) in accordance with the PRISMA statement in the following four databases: PubMed, MEDLINE, PsycINFO, and SPORTDiscus with Full Text. The search strategy was limited to articles published in peer-reviewed journals and to human studies. Nine studies measuring systemic inflammation and discussing its role in chronic disease development were selected for inclusion in this review. The association between markers of systemic inflammation and PTSD was evaluated by the measurement of a variety of systemic inflammatory markers including acute-phase proteins, complement proteins, pro- and anti-inflammatory cytokines, natural killer cells, and white blood cells. In general, systemic inflammatory biomarkers were elevated across the studies in the PTSD groups. There is evidence that PTSD is underpinned by the presence of a systemic low-grade inflammatory state. This inflammation may be the mechanism associated with increased risk for chronic disease in the PTSD population. From this, future research should focus on interventions that help to reduce inflammation, such as exercise. Keywords: cytokines, C-reactive protein, CRP, chronic disease, pro-inflammation, immune system